Tumor Size Is a Critical Factor in Adjuvant Chemotherapy for T3-4aN0M0 Gastric Cancer Patients after D2 Gastrectomy - Shi Chen; Li-Ying Ou-Yang; Run-Cong Nie; Yuan-Fang Li; Jun Xiang; Zhi-Wei Zhou; Ying-Bo Chen; Jun-Sheng Peng (Gastroenterology Research and Practice)
Aim. To investigate whether tumor size is a reasonable indication for adjuvant chemotherapy for T3-4aN0M0 gastric cancer patients after D2 gastrectomy. Method. We performed a retrospective study of 269 patients with a histological diagnosis of T3-4aN0M0 stage gastric cancer who underwent D2 radical surgery at the Sun Yat-sen University Cancer Center or the Sixth Affiliated Hospital of Sun Yat-sen University between January 2006 and December 2010. The follow-up lasted until June of 2015. Chi-square tests and Kaplan-Meier methods were employed to compare the clinicopathological variables and prognoses. Result. For this group of patients, univariate analyses revealed that tumor size (p<0.001), pathological T stage (p<0.001), and tumor location (p=0.025) were significant prognostic factors. Adjuvant chemotherapy did not exhibit prognostic benefits. For patients with tumors larger than 5 cm, univariate analysis revealed that tumor location (p=0.007), Borrmann type (p=0.039), postoperative chemotherapy (p=0.003), and pathological T stage (p<0.001) were significant prognostic factors. Multivariate analysis revealed that postoperative chemotherapy and pathological T stage were independent prognostic factors. Conclusion. Our results imply that tumor size should be a critical factor in the decision to utilize adjuvant chemotherapy for T3-4aN0M0 gastric cancer patients after D2 gastrectomy. Additional randomized controlled trials are required before this conclusion can be considered definitive.